2021
DOI: 10.1155/2021/5017362
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Apelin and Some Angiogenic Factors in the Pathogenesis of Preeclampsia: Apelin-13 as Novel Drug for Treating Preeclampsia and Its Physiological Effects on Placenta

Abstract: Preeclampsia (PE) is one of the commonest causes for maternal and fetal morbidity and mortality. Imbalances of angiogenic factors, oxidative stress, and inflammatory response have a role in the pathogenesis of PE. Data regarding the circulating apelin level and its role in PE remains controversial. This study was formulated to assess the serum apelin level in PE, investigate its correlation with some inflammatory, oxidative stress, and angiogenic proteins in a nitric oxide synthase inhibitor; the N (gamma)-nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Regarding apelin, Hamza et al found that PE-induced rats (L-NAME) showed significantly decreased apelin serum levels [97]. Moreover, they observed significantly increased blood pressure and urine proteins.…”
Section: Preeclampsia (Pe)mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding apelin, Hamza et al found that PE-induced rats (L-NAME) showed significantly decreased apelin serum levels [97]. Moreover, they observed significantly increased blood pressure and urine proteins.…”
Section: Preeclampsia (Pe)mentioning
confidence: 99%
“…Moreover, they observed significantly increased blood pressure and urine proteins. These parameters negatively correlated with the serum apelin level, and exogenous apelin-13 administration significantly improved them, together with an improvement in the placental histoarchitecture [97]. Accordingly, in reduced uterine perfusion pressure PE-induced rats, Wang et al observed that apelin-13 treatment significantly improved the symptoms of PE, suggesting that apelin may be a potential target for treating PE [39].…”
Section: Preeclampsia (Pe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, maternal concentrations of apelin lower than expected may play a key role in the etiology of PE. Circulating apelin concentrations showed a significant negative correlation with mean arterial blood pressure, proteinuria, serum soluble fms-like tyrosine kinase-1 (sFlt-1, a soluble form of VEGF/PLGF receptors which acts as an effective scavenger of VEGF and PLGF and sensitizes maternal endothelium to proinflammatory cytokines, thus inducing endothelial dysfunction and multiorgan damage), soluble endoglin (sEng, that acts as a limiting factor for eNOS activity), and IFN-γ levels in PE compared to control women [72]. Furthermore, a positive correlation of apelin levels with serum placental growth factor (PLGF), VEGF and IL-10 levels, and superoxide dismutase (SOD) and catalase activities was also recognized [72].…”
Section: Oxidative Stress-linked Hypertension Atherosclerosis and Pre...mentioning
confidence: 99%
“…In conclusion, the different results between apelin/APJ/ELABELA expression in various compartments of the placenta and maternal plasma level in PE [ 85 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ] may be explained by several factors such as: apelin corelation with different hormones/growth factors (e.g., VEGF, PLGF, IL-10 [ 154 ]), degree of intensity of PE (mild/severe cases) [ 155 ], or other environmental factors such as maternal age, smoking, or even BMI [ 138 ]. Based on the literature data, apelin inhibited the development of the rat model of PE; administration of apelin twice a day to rats significantly reduced the unfavorable symptoms of PE, which in turn was beneficial in repairing impaired endothelial nitric oxide synthase/NO signaling, and reduced the activation of oxidative stress in the rat model [ 144 ].…”
Section: Placental Pathology and Pregnancy Pathologymentioning
confidence: 99%